PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MENINGKATKAN ETIKA DIGITAL PESERTA DIDIK DI MEDIA SOSIAL - Sukmana, Andi; Hermansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital transformation, marked by the massive use of social media among students, presents new challenges in shaping civic ethics and behavior in the digital space. Various issues such as the spread of false information, hate speech, violations of communication ethics, and low awareness of digital law demonstrate the need to strengthen values education relevant to the digital context. Civics Education plays a strategic role in shaping students' digital ethics through the internalization of Pancasila values, social norms, and the principles of democratic citizenship that are adaptive to technological developments. This study aims to examine the role of Civics Education in improving students' digital ethics in using social media. The research method used is a descriptive qualitative approach with literature review techniques. Data were analyzed through a process of reduction, thematic categorization, and concept synthesis to obtain a comprehensive picture of the contribution of PKn to the formation of digital ethics. The study results show that Civics learning, which contextually integrates digital literacy, digital citizenship, and Pancasila moral values, can increase students' ethical awareness, critical thinking, and responsibility in using social media. Thus, Civics Education plays a significant role in shaping the character of young citizens who are ethical, critical, and responsible in digital life.